INTEGRATION OF THE INTERNET OF THINGS INTO AN INTELLIGENT PARKING SYSTEM - Cleonie Annissa Purnomo; Zhafira Putri Maharani (Komunitas Menulis dan Meneliti (Kolibi), 2023)
The integration of technology into human existence is evident in the progression of the Internet of Things (IoT). This research addresses the critical challenge of parking congestion, offering a thorough examination of a smart parking system application that seamlessly integrates IoT technology. Emphasizing practical implementation, a study conducted in a bustling shopping mall illustrates the effectiveness of the system. Employing tools like Light Dependent Resistor (LDR) sensors, Automatic Number Plate Recognition (ANPR) cameras, and Liquid-Crystal Display (LCD) lights, the system furnishes real-time information accessible via a user-friendly mobile application. The innovative incorporation of a Quick Response (QR) Code for vehicle identification enhances user convenience. Beyond the immediate advantages of locating available parking spaces and facilitating secure payments, the system contributes to economic optimization, decreased traffic congestion, and environmental sustainability. The research underscores the transformative potential of technology in reshaping parking management, offering a valuable template for future initiatives in various contexts.